Pengaruh Struktur Modal dan Profitabilitas terhadap Harga Saham pada Perusahaan sub Sektor Properti dan Real Estate Periode 2020-2024 - Lyra Nur Aulia Hidayah; Eigis Yani Pramularso (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The Indonesian property and real estate sector witnessed significant fluctuations between 2020 and 2024, driven by shifting economic dynamics that impacted stock price stability. In such a volatile environment, strategic management of capital structure and profitability becomes essential to sustain investor trust. This research evaluates how capital structure represented by the Debt to Equity Ratio (DER) and profitability represented by Return on Assets (ROA) affect the stock prices of sub-sector firms listed on the Indonesia Stock Exchange (IDX). Employing a quantitative methodology with purposive sampling, 39 companies were selected as the analytical sample. Statistical processing was performed using multiple linear regression via SPSS 27. The findings reveal that DER has no substantial impact on stock prices, evidenced by a significance value of 0.755 (> 0.05). Conversely, ROA demonstrates a favorable and significant influence, with a significance level of 0.007 (< 0.05). Combined, DER and ROA collectively affect stock prices significantly (Sig. 0.012 < 0.05). Furthermore, the Adjusted R Square of 0.037 indicates that these variables account for 3.7% of stock price variations, while the remaining 96.3% is attributed to external factors beyond the scope of this study.